The Relationship of Organizational Commitment and Employee Job Satisfaction: A Case of Quick Service Restaurants in the Philippines - Nuñez Jr., Danilo P.; Guballo, Jayvie O. (Journal of Management Studies and Development, 2025)
This study explores the relationship between organizational commitment and job satisfaction among employees in selected quick-service restaurants (QSRs) in the Philippines. Using a descriptive-correlational design, data were collected from 279 frontline employees of Jollibee and McDonald’s across Metro Manila. The Organizational Commitment Questionnaire (OCQ) and Job Descriptive Index (JDI) measured various dimensions of commitment and satisfaction. Findings revealed high levels of affective and normative commitment, moderate continuance commitment, and overall high job satisfaction, particularly in career development. A strong positive correlation was found between organizational commitment and job satisfaction, with normative commitment showing the strongest link. No significant differences were observed between local and international QSR brands. These results suggest that emotional and moral factors, more than financial considerations, play a central role in employee satisfaction in the fast-paced food service sector. The study contributes to HR practices by emphasizing the need for purpose-driven work environments and growth opportunities. It concludes that strengthening affective and normative commitment enhances retention and satisfaction. It is recommended that QSRs implement structured recognition programs, leadership development tracks, and internal promotion initiatives to build a more committed workforce. This study is limited by its use of non-probability sampling and focus on Metro Manila, which may affect the generalizability of the results. Practically, these findings guide QSR managers in designing targeted employee engagement and retention strategies. Socially, the study highlights the importance of supporting frontline worker well-being and career growth in high-turnover industries.